2019
DOI: 10.5032/jae.2019.01186
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Longevity and Career Satisfaction in the Secondary Agricultural Education Classroom

Abstract: This study investigated the characteristics and rationale for teacher longevity and success in the secondary agricultural education classroom. The population was 7,300 (N = 7,300) secondary agricultural education teachers in the United States instructing grades 6-12 during 2017-2018. The sample frame was obtained through the National Association of Agriculture Educators membership list and a random sample (n = 187) of the population was selected using the Cochran's (1977) formula for continuous variables. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The importance of administrative support is not foreign to SBAE work. Multiple studies have identified the importance of perceived support among colleagues and administritators within a district to directly affect teacher longevity and success (Clemons & Lindner, 2019;Hasselquist et al, 2017). Professional development (Coldwell, 2017;Rodgers & Skelton, 2014) and teacher mentoring programs (Ingersoll & Kralik, 2004;Ingersoll & Strong, 2011;Hope, 1999) have been identified as methods for building school connectivity.…”
Section: Connectivitymentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of administrative support is not foreign to SBAE work. Multiple studies have identified the importance of perceived support among colleagues and administritators within a district to directly affect teacher longevity and success (Clemons & Lindner, 2019;Hasselquist et al, 2017). Professional development (Coldwell, 2017;Rodgers & Skelton, 2014) and teacher mentoring programs (Ingersoll & Kralik, 2004;Ingersoll & Strong, 2011;Hope, 1999) have been identified as methods for building school connectivity.…”
Section: Connectivitymentioning
confidence: 99%
“…The third construct, curricular connectivity, describes the level of connection SBAE teachers perceive to the curriculum they teach. Existing research suggests the importance of curricular connectivity, with higher teacher autonomy and knowledge of the curriculum relating to increased job satisfaction and intentions to remain in the classroom (Clemons & Lindner, 2019;Kauffman et al, 2002). Thus, teachers with more say in their curriculum, passion, and preparation will perceive higher levels of curricular connectivity.…”
Section: Connectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, SBAE teachers log an average of 55 to 60 hours of work each week (Sorensen et al, 2016). External expectations for SBAE teachers include managing work-based learning programs, collaborating with state and local Career and Technical Education (CTE) officials, managing the local FFA chapter, and engaging with community members and businesses (Clemons & Lindner, 2019;Murray et al, 2011;Sorensen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found the connections teachers have inside and outside the classroom relate to career commitment (Moser & McKim, 2020). Connectivity has been an underlying concept among various areas of focus in SBAE, including self-efficacy, work-life balance, teacher empowerment and professionalism, job satisfaction, school culture, and emotional support (Clemons & Lindner, 2019;Hasselquist et al, 2017;Moser & McKim, 2020;Pearson & Moomaw, 2005;Rinke, 2007;Sass et al, 2011;Sorensen et al, 2016Sorensen et al, , 2017Sorensen & McKim, 2014). Each of the aforementioned concepts intersect with teacher attrition and retention.…”
Section: Introductionmentioning
confidence: 99%